Systematizing coaches' 'eye for talent': Player assessments based on expert coaches' subjective talent criteria in top-level youth soccer. Issue 5 (October 2017) - Jokuschies, Nina; Gut, Vanessa; Conzelmann, Achim
Although talent selection in professional soccer mainly relies on the subjective judgment of scouts and coaches, little is known to date about top-level soccer coaches' conceptions of talent. Drawing on a constructivist approach, this mixed method study intends to give an in-depth insight into coaches' subjective talent criteria and to investigate the validity and reliability of their player assessments based on these criteria. Five national youth soccer coaches were examined using semistructured inductive interviews and the repertory grid technique. The results reveal experienced soccer coaches' subjective talent criteria and indicate the multidimensional nature of their concepts of talent. There is a high correlation (−.57 ≤ rs  ≤ −.81) between the coaches' assessment of their players based on their own talent criteria and their previous evaluation of these players' overall potential, indicating criterion validity. Repeated evaluations of the players according to a coach's talent criteria display an adequate test–retest reliability over a period of 10 weeks.